2022
DOI: 10.1002/jcp.30891
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and vascular calcification in chronic kidney disease: Lessons learned from the past to improve future therapy

Abstract: Chronic kidney disease-mineral and bone disorders (CKD-MBD) is a common complication of CKD Stages 3-5. Hyperphosphatemia is one of the major metabolic components of CKD-MBD, frequently resulting in vascular calcification (VC) in advanced-stage patients. Also, a long duration of renal replacement therapy can cause the worsening of VC, leading to increased cardiovascular morbidity and mortality. Vascular smooth muscle cells play an important role in the development of VC through osteochondrogenic transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…CKD is associated with increased morbidity and mortality of cardiovascular disease, and its poor prognostic outcome is also associated with CKD-MBD. According to studies, endothelial dysfunction, atrial stiffness, and vascular calcification are all significantly influenced by CKD-MBD 20 . In this study, Age, BUN, SUA, P, and TG were identified as independent risk factors for vascular calcification in patients with CKD5.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is associated with increased morbidity and mortality of cardiovascular disease, and its poor prognostic outcome is also associated with CKD-MBD. According to studies, endothelial dysfunction, atrial stiffness, and vascular calcification are all significantly influenced by CKD-MBD 20 . In this study, Age, BUN, SUA, P, and TG were identified as independent risk factors for vascular calcification in patients with CKD5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large number of reports have shown that vascular calci cation is an active and highly regulated complex pathological process similar to bone development (12). Vascular calci cation is mainly characterized by increased stiffness and decreased compliance of the vascular wall, accompanied by hypertension, atherosclerosis, diabetes and chronic kidney disease, which is one of the important reasons for the high morbidity and mortality of cardiovascular and cerebrovascular diseases (13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…CKD is associated with increased morbidity and mortality of cardiovascular disease, and its poor prognostic outcome is also associated with CKD-MBD. According to studies, endothelial dysfunction, atrial stiffness, and vascular calci cation are all signi cantly in uenced by CKD-MBD 20 . In this study, Age, BUN, SUA, P, and TG were identi ed as independent risk factors for vascular calci cation in patients with CKD5.…”
Section: Discussionmentioning
confidence: 99%